2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--29997
|View full text |Cite
|
Sign up to set email alerts
|

Board 28: Work in Progress: How Do Students Respond to Active Learning? A Coding Guide for a Systematic Review of the Literature

Abstract: is a Ph.D candidate in the Science, Technology, Engineering, and Mathematics (STEM) Education program at University of Texas at Austin. He has worked on NSF grant projects related to students' resistance to active learning and how funding impacts STEM graduate students. His own dissertation work examines learning, marginality, and environmental citizen scientists. He has a B.S. and M.Eng in Environmental Engineering both from Texas Tech University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…After three rounds of refining the coding form and its categories, at least one researcher coded each of the 412 qualifying studies for details such as discipline, class size, type of active learning, type of affective response, and conclusions regarding student responses. Summary results of the coding are presented in this paper, and more detail about the software, coding procedures, coding form, and data management for this collaborative systematic review project are reported elsewhere [14]. Finally, we developed three "quality score" rubrics -one to apply to quantitative studies, one for qualitative studies, and one for studies that used mixed methods -to assess the quality of each study, and at least one researcher used coding data and other study details to calculate a quality score for each of the 412 studies.…”
Section: Methodsmentioning
confidence: 99%
“…After three rounds of refining the coding form and its categories, at least one researcher coded each of the 412 qualifying studies for details such as discipline, class size, type of active learning, type of affective response, and conclusions regarding student responses. Summary results of the coding are presented in this paper, and more detail about the software, coding procedures, coding form, and data management for this collaborative systematic review project are reported elsewhere [14]. Finally, we developed three "quality score" rubrics -one to apply to quantitative studies, one for qualitative studies, and one for studies that used mixed methods -to assess the quality of each study, and at least one researcher used coding data and other study details to calculate a quality score for each of the 412 studies.…”
Section: Methodsmentioning
confidence: 99%